The role of physical activity in preventing obesity in midlife women - Dąbrowska, Jolanta; Dąbrowska-Galas, Magdalena; Naworska, Beata; Wodarska, Magdalena; Plinta, Ryszard (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Obesity is one of the most common nutrition-related disorders worldwide and one of the major health problems in menopausal women, which significantly worsens the quality of life and can lead to severe diseases or even premature death. The aim of the study was to evaluate the relation between physical activity in different domains undertaken by menopausal women while performing daily activities and their body mass index (BMI). Material and methods : The study was conducted on a random sample of 400 healthy Polish women aged 45-55. The questionnaire contained questions concerning the respondents’ socio-economic status, medical history and the long format of the International Physical Activity Questionnaire was used. Results: Fifty-one percent (50.6%) of women had normal body mass, 43.75% of respondents were overweighed and 5.65% of women were obese. A moderate physical activity level was presented by most midlife women in domestic and garden domain, active transportation and leisure time. Pearson’s correlation showed that such factors as age, education and physical activity level in different domains have a significant correlation with BMI. Conclusions : Most respondents presented a moderate physical activity level in all domains except work, where the respondents had a high physical activity (PA) level. A high PA level especially at work (r = –0.5788) and during leisure time (r = –0.5175) strongly correlate with lower BMI.